Pemberdayaan Masyarakat Pada Program Prodamas Sebagai Upaya Peningkatan Sarana & Prasarana Lingkungan Di Kel Campurejo Kecamatan Mojoroto Kota Kediri - Eka Askafi; Heni Sulistiyowati (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Growth of town that is quickly directly affects at development of elementary infrastructure and service of public that is it is of course requires a real big defrayal. This thing claims government of town to do efesiensi and effectivity in development defrayal, because limitation of government of town in providing development fund. Including specifying sectors which can be delivered its the management to public as a form of participation. Prodamas as one of program penanggulangan poorness of urban brings concept differing from program before all, be through enableness approach of public emphasizing at participation aspect and independence causing is reached sustainable development in 3 life aspect that is economics, social and physical of area (Tree power). This research aim to study participation of public in development of environmental infrastructure passed Enableness Program Sub-district Public (Prodamas), with qualitative descriptive analytical method to analyse form and level of partsipasi public at development of area infrastructure, and quantitative analytical method, to analyse influence the relation of public economics social with form of participation. Result of research shows existence of antusiasme involvement of public in every development step of environmental infrastructure in so many form. Responder taking part in in each development step of indicating that environmental infrastructure is responder has done good cooperation with government as conceptor existence of program Prodamas. Indication existence of this cooperation, indicates that form of participation of public has resided in at partnership level, medium of existence Enableness Program Sub- district Public (Prodamas) in sub-district Campurejo stays at partnership level. Recommendation given in this research is entangling of all public in development of environmental infrastructure without reference to difference of condition of economics social, and improvement of socialization intensity Enableness Sub-district Public (Prodamas) by government that this program stays at partnership level, where at this level participation of public haves the power of negotiation with power owner in doing planning, execution, observation and evaluation.